Problematika Pemberdayaan dan Pengembangan Sumber Daya Manusia di Sekolah Menengah Pertama Berbasis Pesantren - Desi Eri Kusumaningrum; Raden Bambang Sumarsono; Imam Gunawan (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2017)
Abstract: The purpose of this research is to describe the problematic of empowerment and human resource development in junior high school based on pesantren in East Java. This research is conducted with qualitative approach. The subjects of this study are school administrative staff (tenaga administrasi sekolah / TAS), teachers, and principals. Data collection techniques are interviews. Subsequently used as material in carrying out focus group discussion (FGD). Data analysis is done through three steps, namely: data reduction; display data; and conclusion drawing / verifying. The results showed that school problems in the empowerment of principals are: the duty of boarding school board; communication barriers and coordination with pesantren; communication barriers with teachers and administrative staff (tenaga administrasi sekolah / TAS); and task delegation. School problems in teacher empowerment are: the ratio of teacher-student numbers is not proportional; some teachers teach at other educational institutions; lack of understanding how to educate students according to the vision and mission of schools and pesantren; and less optimal teaching supervision. School problems in the empowerment of administrative staff (tenaga administrasi sekolah / TAS) are: the limited infrastructure of the school office; number of TAS personnel; and mastery of information and communication technology (ICT). Human resource development is done in two ways, namely group development and individual development. Abstrak: Tujuan Penelitian ini adalah mendeskripsikan problematika pemberdayaan dan pengembangan sumber daya manusia di sekolah menengah pertama (SMP) berbasis pesantren di Jawa Timur. Penelitian ini dilakukan dengan pendekatan kualitatif. Subjek penelitian ini adalah tenaga administrasi sekolah (TAS), guru, dan kepala sekolah. Teknik pengumpulan data adalah wawancara. Selanjutnya dijadikan bahan dalam melaksanakan focus group discussion (FGD). Analisis data dilakukan melalui tiga langkah, yaitu: data reduction; data display; dan conclusion drawing/verifying. Hasil penelitian menunjukkan bahwa permasalahan sekolah dalam pemberdayaan kepala sekolah adalah: adanya tugas menjadi pengurus pesantren; hambatan komunikasi dan koordinasi dengan pesantren; hambatan komunikasi dengan para guru dan TAS; dan pendelegasian tugas. Permasalahan sekolah dalam pemberdayaan guru adalah: rasio jumlah guru-siswa belum proporsional; beberapa guru mengajar di lembaga pendidikan lain; kurangnya kesepahaman cara mendidik siswa sesuai visi dan misi sekolah dan pesantren; dan kurang optimalnya supervisi pengajaran. Permasalahan sekolah dalam pemberdayaan TAS adalah: terbatasnya sarana prasarana kantor sekolah; jumlah personil TAS; dan penguasaan Teknologi Informasi dan Komunikasi (TIK). Pengembangan sumber daya manusia (SDM) dilakukan dengan dua cara, yaitu pengembangan yang bersifat kelompok dan pengembangan yang bersifat individu.